Cystathionine γ-lyase deficiency mediates neurodegeneration in Huntington’s disease - Paul, Bindu D. (Nature, 2014)
Huntington’s disease is an autosomal dominant disease associated with a mutation in the gene encoding huntingtin (Htt) leading to expanded polyglutamine repeats of mutant Htt (mHtt) that elicit oxidative stress, neurotoxicity, and motor and behavioural changes(1). Huntington’s disease is characterized by highly selective and profound damage to the corpus striatum, which regulates motor function. Striatal selectivity of Huntington’s disease may reflect the striatally selective small G protein Rhes binding to mHtt and enhancing its neurotoxicity(2). Specific molecular mechanisms by which mHtt elicits neurodegeneration have been hard to determine. Here we show a major depletion of cystathionine γ-lyase (CSE), the biosynthetic enzyme for cysteine, in Huntington’s disease tissues, which may mediate Huntington’s disease pathophysiology. The defect occurs at the transcriptional level and seems to reflect influences of mHtt on specificity protein 1, a transcriptional activator for CSE. Consistent with the notion of loss of CSE as a pathogenic mechanism, supplementation with cysteine reverses abnormalities in cultures of Huntington’s disease tissues and in intact mouse models of Huntington’s disease, suggesting therapeutic potential.